Immunological blockade of adipocyte inflammation caused by increased matrix metalloproteinase‐cleaved osteopontin in obesity. (16th March 2015) - Leitner, Lukas; Schuch, Karina; Jürets, Alexander; Itariu, Bianca K.; Keck, Maike; Grablowitz, Viktor; Aszmann, Oskar C.; Prager, Gerhard; Staffler, Günther; Zeyda, Maximilian; Stulnig, Thomas M.
Abstract : Objective: Osteopontin (OPN) is upregulated in adipose tissue (AT) in obesity and contributes to subclinical inflammation, adipocyte dysfunction, and insulin resistance. OPN effects can be increased by cleavage by matrix metalloproteinases (MMP). This study aimed at investigating the presence of OPN cleavage products in human AT in obesity and their impact on adipocyte function and immunological blockade of these effects. Methods: AT of severely obese and control donors was investigated for OPN and MMP expression and the presence of OPN cleavage fragments. Primary adipocytes were isolated from human donors for in vitro investigation of cleaved OPN effects. Results: OPN and MMP‐9 expression was highly correlated in AT from obese donors, and increased levels of cleaved OPN were detected in AT from obese individuals. The in vitro effect of OPN on adipocyte inflammation and insulin resistance was enhanced by protease cleavage, which could finally be blocked with a monoclonal antibody directed against the MMP cleavage site of OPN. Conclusions: These findings show that MMP cleavage of OPN in AT occurs in obesity, thereby enhancing OPN's inflammatory and pro‐diabetic activity on adipocytes. Specifically targeting MMP‐cleaved OPN opens avenues for prevention and treatment of obesity‐induced type 2 diabetes.